Homo historicus coby plastický, nebo elastický autodomestikant? Několik poznámek na okraj analogií mezi biologickou a kulturní evolucí - Horský, Jan (Lidé města, 2024)
Biosemiotics (Barbieri, Markoš) is used in the discussions of analogies between biological species and (human) cultures. The theory of “frozen evolution” contends that biological species behave the same in their elastic stage of development as cultures do in their development (Flegr). In biosemiotics, the narrative is attributed to life itself at all of its developmental stages (Markoš). This all gives clear ground for the humanities and social sciences, especially for the historical sciences, to enter discussions with biology and to apply their discoveries with regards to the character of cultural development (here, culture is understood as a semiotic system). Primarily, it is necessary to differentiate between the interpretative analogies of species and cultures (which only have a noetic and methodological function) and ontic analogies (which have a real congruence with the dynamic structures of “species” and “cultures”). Historical sciences enter this discussion using methods that are more open to interpretation and are semiotically more volatile (polysemic) than those of biology. The humanities prove to offer an interpretation of the gradual growth of the ability to control aggression, which rivals the interpretations of evolutionary anthropology and biology. Thus, the need to rethink in more detail what the comparable counterpart to biological species is arises, especially if we wish to describe the elastic phase of its development using an analogy to the development of human cultures (the following pair seems to come to mind: higher taxons – culture; in comparison to this first pair, there is also one that is one level lower, yet rather allows for comparison: species – selected configurations of cultural contents, cultural variants). It also shows the need to analytically differentiate culture from human behaviour/actions influenced by culture so that it could truly be a comparison of the elasticity of a species and the elasticity inside a certain circle of cultural contents (variants). At those places where biosemiotics takes interest in the origins of human reflexive spirituality and of the experience of transcendence in the last several millennia (Markoš), it can productively cross paths with the civilisationist theory of “axial transformation” (Arnason). However, there is always the issue of how to scientifically connect external signs with the internal experiences of the studied actors. The relationship between external “behavior” (behavior, pratiques, Verhalten) and inner “mental representations” is always discussable from the perspective of science only when using a certain degree of hypothesis. In constructing this image, it shall always be affected by certain meta-physical, meta-biological, or meta-historical assumptions, stemming from, for example, the philosophical analysis of spirituality, transcendental consciousness, or phenomena.